Chemotherapy is superior to checkpoint inhibitors after radical surgery for urothelial carcinoma: a systematic review and network meta-analysis of oncologic and toxicity outcomes. (January 2022) - Laukhtina, Ekaterina; Sari Motlagh, Reza; Mori, Keiichiro; Katayama, Satoshi; Rajwa, Pawel; Yanagisawa, Takafumi; Quhal, Fahad; Mostafaei, Hadi; Grossmann, Nico C.; König, Frederik; Aydh, Abdulmajeed; Pradere, Benjamin; et al.
Graphical abstract: Highlights: The use of ICIs does not appear to be an attractive alternative to chemotherapy in the adjuvant setting in patients treated with radical surgery for urothelial carcinoma. We found a marginal benefit of adjuvant chemotherapy after radical cystectomy. Adjuvant chemotherapy with high certainty was the best treatment after radical nephroureterectomy. Abstract: Objective: To determine the oncologic and toxicity outcomes of adjuvant immunotherapy with immune checkpoint inhibitors (ICIs) compared to adjuvant chemotherapy in patients treated with radical surgery for urothelial carcinoma (UC). Methods: We used the Bayesian approach in the network meta-analysis of different therapy regimens compared to observation or placebo. Results: Nine studies comprised of 2, 444 patients met the eligibility criteria. In bladder UC, chemotherapy, atezolizumab, and nivolumab did not improve disease progression compared to observation/placebo. In upper tract UC (UTUC), chemotherapy was significantly associated with a lower likelihood of disease progression compared to observation/placebo, while atezolizumab and nivolumab were not. Based on the analysis of the treatment ranking, adjuvant chemotherapy appeared as the best treatment approach in both bladder UC and UTUC. The risk of adverse events with ICIs was comparable to that of observation/placebo. Conclusion: Our analysis suggests a superior oncologic benefit to adjuvant chemotherapy over ICIs in patients treated with radical surgery for both bladder UC and UTUC.